Are hospital services for self-harm getting better? An observational study examining management, service provision and temporal trends in England - Cooper, J; Steeg, S; Bennewith, O; Lowe, M; Gunnell, D; House, A; Hawton, K; Kapur, N (BMJ Publishing Group, 2013)
OBJECTIVES: To describe the characteristics and management of individuals attending hospital with self-harm and assess changes in management and service quality since an earlier study in 2001, a period in which national guidance has been available. DESIGN: Observational study. SETTING: A stratified random sample of 32 hospitals in England, UK. PARTICIPANTS: 6442 individuals presenting with 7689 episodes of self-harm during a 3-month audit period between 2010 and 2011. OUTCOME: Self-harm episodes, key aspects of individual management relating to psychosocial assessment and follow-up, and a 21-item measure of service quality. RESULTS: Overall, 56% (3583/6442) of individuals were women and 51% (3274/6442) were aged under 35 years. Hospitals varied markedly in their management. The proportion of episodes that received a psychosocial assessment by a mental health professional ranged from 22% to 88% (median 58%, IQR 48-70%); the proportion of episodes resulting in admission to general hospitals varied from 22% to 85% (median 54%, IQR 41-63%); a referral for specialist mental health follow-up was made in 11-64% of episodes (median 28%, IQR 22-38%); a referral to non-statutory services was made in 4-62% of episodes (median 15%, IQR 8-23%); 0-21% of episodes resulted in psychiatric admission (median 7%, QR 4-12%). The specialist assessment rate varied by method of harm; the median rate for self-cutting was 45% (IQR 28-63%) vs 58% (IQR 48-73%) for self-poisoning. Compared with the 2001 study, there was little difference in the proportion of episodes receiving specialist assessment; there was a significant increase in general hospital admission but a decrease in referrals for specialist mental health follow-up. However, scores on the service quality scale had increased from a median of 11.5-14.5 (a 26% increase). CONCLUSIONS: Services for the hospital management of self-harm remain variable despite national guidelines and policy initiatives. We found no evidence for increasing levels of assessment over time but markers of service quality may have improved. This paper forms part of the study 'Variations in self-harm service delivery: an observational study examining outcomes and temporal trends'. The National Institute for Health Research Clinical Research Network (NIHR CRN) Portfolio database registration number: HOMASH 2 (7333). The NIHR Coordinated System for gaining NHS Permission (CSP) registration number: 23226.